Observer-Based Sliding Mode Control for Networked Fuzzy Singularly Perturbed Systems Under Weighted Try-Once-Discard Protocol - Wang, Jing; Yang, Chengyu; Xia, Jianwei; Wu, Zheng-Guang; Shen, Hao (IEEE transactions on fuzzy systems, 2022)
In this article, the sliding mode control issue is investigated for a class of discrete-time Takagi-Sugeno fuzzy networked singularly perturbed systems via an observer-based technique. Moreover, to process the measurement output and schedule the transmission sequence for relieving the communication burden, a logarithmic quantizer and a weighted try-once-discard protocol are synthesized, which can further improve the network bandwidth utilization in networked control systems. Based on the fuzzy observer states, a novel fuzzy sliding surface is established by considering the singularly perturbed parameter properly, and we endeavor to synthesize a sliding mode control law such that the reachability of the prescribed sliding surface could be guaranteed. In addition, by virtue of the convex optimization theory and Lyapunov approach, sufficient conditions are developed to guarantee the asymptotic stability of the sliding mode dynamics as well as the error system with an expected H_{∞ } performance. Finally, a verification example is presented to illustrate the feasibility and effectivity of the proposed method.